Psychological Aspects of the Effectiveness of the Athletes' Team on the Example of Handball. - Prof. Askarbay Niyazov (Genius Publishing Group, 2024)
This article discusses the general concept of the game, the main psychological aspects of the team of athletes playing handball, the psychological characteristics of the general game, the motor activity of handball players in the game, the rules of handball, the description of five standard throws of the game. This affects the provision of high results of playing activities in competitions when playing handball, the formation of general psychological qualities of the athlete's personality, as well as specific features of a sports nature. About the importance in the formation of a harmonious combination of the player's personal characteristics, active participation in game interaction and programming the team's activities as a whole to achieve certain results.
Keywords: Handball; psychological aspects; harmonic combination; specific characteristics of the athlete.